ANÁLISE DAS CONDIÇÕES DE ILUMINAÇÃO NATURAL EM AMBIENTE DE TRABALHO EM EDIFICAÇÃO HISTÓRICA - Barasuol, Fernanda; Correa, Celina (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The use of natural lighting in work environments, in addition to the benefits of energy efficiency, is essential for user well-being and quality of work. In historical buildings, where interventions are controlled or prohibited, the adaptation of lighting to the demand for new uses is necessary and complex. This work aims to evaluate the natural light conditions in a technical work environment in a historical heritage building in Bagé, RS, so that solutions or adjustments can be increased. The methodology used was computer simulation of the ambient illuminances through the program Rhinoceros and plugin DIVA, in pre-established days and times, in addition to dynamic simulations. Structured interviews with users of the environment were carried out. There were spots with high illuminances and light with potential for brightness at certain times causing users dissatisfaction, keeping the windows closed. In contrast, often the amount of light has not reached the minimum levels of illumination required by the current standard. Due to the historical characteristics, no change in facade was considered. The need for adjustments such as the replacement of colors, the use of internal blinds and the awareness of the importance of sunlight and the control of artificial light are confirmed.